Accounting Perspective of Malang Bantengan Culture with an Ethnomethodological Approach - Utami, Riski Nur; Sopanah, Ana; Bahri, Syamsul (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2025)
Purpose: This research aims to uncover the values of local wisdom contained in "Bantengan" and financing in the art of "Bantengan". Methodology: The type of method used is a qualitative method with an ethnomethodological approach where the author analyzes a culture in the form of the art of "Bantengan" which focuses on "Reality" or the reality of social aspects in daily life. Finding: The results of the study show that the art of bantengan contains the values of wisdom which include "Guyup Rukun" (Togetherness), "Kekang Control" (Guide), and "Paseduluran" (Brotherhood). Implication: The accounting practice in this case the financing of the bantengan does not record or bookkeeping in any form. Funds are sourced from personal money and player dues only. Originality: The novelty of this research lies in the disclosure of the values of local wisdom in the art of Bantengan which is integrated with the practice of non-formal financing without accounting records, which has not been widely studied in the context of ethnomethodology.